2022
DOI: 10.1186/s12904-022-01019-x
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of an advance care planning training program for practice professionals in Japan incorporating shared decision making skills training: a prospective study of a curricular intervention

Abstract: Background We developed a novel training program for health care professionals that incorporated shared decision making (SDM) skills training into an advance care planning (ACP) training course, the first in Japan. This study aimed to assess the training program’s impact on health care professionals’ knowledge, skill, attitudes, and confidence to initiate ACP. Methods Using the novel Japanese educational program, we evaluated the effect of 8-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
10
0
2
Order By: Relevance
“…In our previous report, the training program integrating ACP and SDM was found to improve SDM skills through the use of SDM-Q series and confidence of ACP practice [ 22 ]. In the study, the effect of the interprofessional SDM (Group’s SDM) was not assessed, but through group discussions using this measure, there is a possibility that patient-centered multidisciplinary collaboration can progress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous report, the training program integrating ACP and SDM was found to improve SDM skills through the use of SDM-Q series and confidence of ACP practice [ 22 ]. In the study, the effect of the interprofessional SDM (Group’s SDM) was not assessed, but through group discussions using this measure, there is a possibility that patient-centered multidisciplinary collaboration can progress.…”
Section: Discussionmentioning
confidence: 99%
“…“Training on SDM competency in advance care planning” is a program that was conducted during the SDM workshops for ACP, and it included three workshops conducted over a period of 6 months [ 22 ]. In the first and third workshops, the participants were trained in one-to-one conversation using the related SDM questionnaires [ 18 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shared decision-making (SDM) has been considered an important skill in implementing ACP [ 6 ]. A fact-finding survey of SDM implemented in primary care outpatient services in Japan revealed that the level of SDM among doctors and patients with outpatient nurses was significantly high [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the author reported that the corrections concerning the correct sequence of the reference list were not carried out.…”
mentioning
confidence: 99%